The effect of web-based social networking on consultancy - Shaikh, Humaiz; Maher, Zulfikar Ahmad; Raza, Ali; Abdullah, Mirza Manirajah; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2019)
Social networking has become a fact that we cannot live without even if we try. It has become a day to day activity or even yet a chore. Where we share our life experiences. We have all become its slave! Social networks bring many benefits to the user and the world at large. These advantages from an expert perspective includes sharing of information, collaboration, promote products and services, building a group community, donations etc. This paper provides a review of the Effect of Web-based Social Networking on Consultancy.